BENTUK PENYAJIAN SILEK PANGIAN DALAM ACARA BAKAUA ADAT (BAKATOMPAT)DI NAGARI SUNGAI LANSEK KECAMATAN KAMANG BARU KABUPATEN SIJUNJUNG - Yendi Putri, Shakila; Kadir, Tulus Handra (Universitas Negeri Padang, 2025)
This research aims to describe and unveil the presentation of Silek Pangian in the Bakau Adat (Bakatompat) event in Nagari Sungai Lansek, Kamang Baru District, Sijunjung Regency. This type of research is qualitative with a descriptive approach. The research instrument is the researcher themselves, assisted by supporting instruments such as writing materials and a camera. Data was collected through literature study, observation, interviews, and documentation. The steps in data analysis include data collection, data classification, data description, and data conclusion. The research results show that the form of Silek Pangian presentation in the Bakaua Adat (Bakatompat) event in Nagari Sungai Lansek, Kamang Baru District, Sijunjung Regency includes movement, accompanying music, floor patterns, makeup and costumes, and the time and place of the performance. The movement of Silek Pangian resembles a prayer, with greetings, four-step motions, slicing movements, thrusting actions, punching movements, upward strikes, locking movements, and closing actions. In the Silek Pangian performance, traditional Minangkabau instruments such as the talempong pacik (canang), gandang tambuah, and krincing are used as accompaniment, along with a layout of straight and circular patterns that depict the interaction between the martial artist and opponent. The Silek Pangian performance also features traditional Minangkabau attire comprising a black kurung shirt, side cloth, galembong, and peci, and is held outdoors in the evening. This performance is not merely entertainment but also a medium for education and the transmission of cultural values and identity to the younger generation, embodying strong spiritual, social, and cultural significance